Record of Celeus obrieni (Aves: Piciformes: Picidae) in the Cantão State Park: implications for species conservation and boundary consolidation of the first integral protection conservation unit in Tocantins, Brazil - Dornas, Túlio; Georgiadis, George (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Kaempfer’s woodpecker (Celeus obrieni Short, 1973) is an endangered species and a Brazilian endemic. Numerous records of the species have been made in the Cerrado biome and portions of eastern Amazonia. However, sightings of this species were never within the limits of Integral Protection Areas. Here, we present the record of Celeus obrieni in a 600 hectares fragment of semideciduous forest with bamboo in the Administrative and Visitor Reception Center of the Cantão State Park (CSP), in western Tocantins, Brazil. Although this area is under public domain, belonging to Tocantins state, its limits have not yet been incorporated into the legal limits of the CSP. To include this area within the legal limits would result in significant gains in the protection and conservation of the species and further reinforce the importance of the CSP for the conservation of Cerrado-Amazon ecotone biodiversity.
Keywords: Celeus obrieni; Endangerd species; Cantão State Park; Protect areas